Health Promotion Perspectives on Self-Efficacy and Psychosocial Determinants of Sustainable Sanitation Behavior in Rural Indonesia - Marylin S. Junias; Apris A. Adu; Sarci Magdalena Toy; Eryc Haba Bunga; Claudya S.V Sudarmadji; Agus Setyobudi; Mas'Amah Mas'Amah; Irwan Budiyono (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Open defecation remains a major public health challenge in rural and dryland regions, where infrastructural constraints and psychosocial barriers intersect. This study analyzed the associations between self-efficacy, community perceptions, and basic sanitation infrastructure and sanitation behavior in East Baumata Village, Kupang Regency. Method: An analytic, community-based cross-sectional survey was conducted with n = 128 randomly sampled household heads, using theory-informed structured questionnaires and observational checklists to capture psychosocial and infrastructural determinants. Data were analyzed using descriptive statistics, ?² tests, and multivariable logistic regression reporting adjusted odds ratios (aOR) and p-values. Result: Most respondents demonstrated favorable knowledge and attitudes; self-efficacy was strongly associated with consistent latrine use (aOR ? 16.2, p < 0.001). Community perceptions and latrine distance were significant in bivariate analyses (p = 0.0153 and p = 0.001, respectively) but were not significant after adjustment (p > 0.05), suggesting their associations may be accounted for by self-efficacy (no formal mediation was tested). Water availability was not associated with the outcome (p = 0.985) when minimum access was present. These findings align with behavioral models emphasizing perceived control, self-regulation, and normative influences in health promotion. Conclusion:Policy and program design should prioritize self-efficacy–building interventions (e.g., peer modeling, guided practice) and norm-focused community engagement, alongside proximity-sensitive infrastructure investments, to enhance sustainability. This research contributes to refining the implementation of Indonesia’s Community-Based Total Sanitation program and offers insights for global strategies aimed at achieving SDG 6.2.